The Effects of Professor Gender on the Post-Graduation Outcomes of Female Students - Hani Mansour; Daniel I. Rees; Bryson M. Rintala; Nathan N. Wozny (Center for Economic Studies and ifo Institute (CESifo), 2022)
Although women earn approximately 50 percent of science, technology, engineering and math (STEM) bachelor's degrees, more than 70 percent of scientists and engineers are men. We explore a potential determinant of this STEM gender gap using newly collected data on the career trajectories of United States Air Force Academy students. Specifically, we examine the effects of being assigned female math and science professors on occupation choice and postgraduate education. We find that, among high-ability female students, being assigned a female professor leads to substantial increases in the probability of working in a STEM occupation and the probability of receiving a STEM master's degree.
Keywords: I20; J16; J24; 330